Evaluation of Real-Time Data Recording Performance Utilizing the Solar Guardian Application at Rooftop Solar Power Plants - Anugra, Rifky; Sofijan, Armin (JATISI, 2025)
The Solar Guardian application was developed as a real-time monitoring solution for rooftop solar power plants to improve system efficiency and reliability. This study evaluates the performance of Solar Guardian in recording and analyzing the main parameters of a polycrystalline panel-based solar power plant with a maximum power of 100 Wp, a maximum voltage of 20 V, and a maximum current of 5.5 A. This system uses a 100 Ah VRLA battery, with monitoring of the panel output voltage, battery charging and discharging current, and energy storage efficiency. The results show that Solar Guardian is able to increase the efficiency of solar power plant monitoring by up to 20%, with early detection of system anomalies, such as decreased solar panel performance and power imbalance in the battery. This application also allows users to access operational data in real time through a cloud-based interface, making it easier to manage power and optimize energy utilization. In addition, the integration of IoT technology in Solar Guardian allows automation in data recording, thereby reducing delays in maintenance decision making. With the implementation of this application, solar power plants can operate more stably, increase energy storage efficiency, and optimize carbon emission reductions of up to 35.86 kg CO₂ per day. Keywords: Solar Guardian, solar power plant, real-time monitoring, energy efficiency, early detection